A Review On Hindering Factors To Maximize Healthcare Potential In Poverty And Islamic Way Of Promoting Health - Farrah Farzana Abdullah; Mohd Rahman Omar (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2024)
INTERNATIONAL FAMILY HEALTH CONFERENCE 2019(I-FaH 2019) Health Intervention Towards Community Wellness Held at Oriental Crystal Hotel, Kajang, Selangor, Malaysia On 4-5th September, 2019 Malaysian Journal of Medicine and Health Sciences (Vol.15 Supp 4)